THE EFFECT OF EDUCATION THROUGH YOUTUBE TO THE MASTERY OF KNOWLEDGE AND ATTITUDES ABOUT COMPLEMENTARY FEEDING OF MOTHERS WHO HAVE CHILDREN UNDER TWO YEARS AT BUBUTAN SUB-DISTRICT, SURABAYA - Hayati Solikhah; Siti Sulandjari (JURNAL KESMAS DAN GIZI (JKG), 2022)
Stunting is a nutritional problem in children under 5 years old as seen on the z-score value from the measurement of height for age <-2 standard deviations (stunted) or <-3 (severely stunted). Stunting shows the condition of children who fail to thrive due to chronic malnutrition. In addition to having an impact on physical growth disorders, stunting also affects brain development. Stunting conditions are only seen after the child is over 2 years old and the situation can be more serious if it is not catch-up growth. One of the efforts to reduce the nutritional problems of stunting children is to change the knowledge, attitudes and behavior of parents through education. The purpose of this study was to determine the effect of using videos through YouTube on mothers' mastery and attitudes about MP-ASI in Bubutan District, Surabaya. This research is a quasi-experimental type of research with a nonequivalent control groupThe study sample included 36 mothers who had children under the age of 2 years, divided into experimental and control groups, with 18 respondents in each group. The results of the paired sample t-test showed that there was a significant difference (p = 0.000) between the pretest and posttest values of knowledge and attitudes in both groups. The independent sample t-test (p = 0.000) showed a difference in the average knowledge and attitudes between the use of video media through YouTube and reading sheet about complementary foods. The conclusions of this study indicate that using videos through YouTube can increase the mastery of knowledge and attitudes of mothers who have children under two years about complementary feeding and is better than using reading sheet about complementary foods.